Patient-centric care: Unveiling the potential of wearable electronics in clinical practice - Zhao, Pengcheng; Xu, Jie; Han, Mengdi (Wearable Electronics, 2024)
Wearable electronics have the capability to monitor human activities and various physiological indicators in a real-time, continuous, non-invasive, and wireless manner, making them a valuable complement to traditional clinical health monitoring technologies. Currently, the adoption of specialized and reliable wearable electronics for disease diagnosis, monitoring, and treatment is flourishing. This article delves into the development of wearable electronics from a clinical application perspective, examining the application modes, mechanisms, and benefits of (1) commercial wearable electronics, (2) customized wearable electronics, and (3) customized flexible electronics in clinical settings. The focus of the article is on analyzing the diverse forms of electronic systems utilizing mechanical, thermal, optical, electrophysiological, and electrochemical technologies, in alignment with clinical application requirements. Furthermore, the article outlines the challenges encountered by wearable electronics in clinical environments and discusses potential future directions for wearable electronics in clinical applications. [Display omitted] •This review introduces various wearable electronics deployed on patent subjects.•This review classifies wearable electronics into three types according to their levels of commercialization.•This review discusses challenges and future opportunities of wearable electronics.